Engineered Lysin-Derived Peptide as a Potent Antimicrobial for Acne Vulgaris - Uri Sela; Ryan D. Heselpoth; Vincent A. Fischetti (Antibiotics)
Background/Objectives: Acne vulgaris is a skin disorder that affects millions worldwide, with Cutibacterium acnes playing a key role in its inflammation. Antibiotics reduce C. acnes and inflammation, but growing antibiotic resistance has limited their efficacy. Additionally, other common acne treatments with bactericidal activity, like benzoyl peroxide, cause irritation, dryness, and peeling. To fulfill the unmet need for alternative therapies, our strategy focused on identifying potent phage lysins and/or their derived cationic peptides. Methods: The C-terminal cationic antimicrobial peptide of the Prevotella intermedia phage lysin PlyPi01 was synthesized along with several sequence-engineered variants in an attempt to enhance their bactericidal efficacy. In vitro bacterial killing assays evaluated the potency of the lysin-derived peptide derivatives against C. acnes and Staphylococcus aureus, another skin bacterium associated with acne. Antibacterial activity was assessed both in conditions simulating the human skin and in combination with retinoids. Results: The variant peptide P156 was engineered by adding arginine residues at both the N- and C-terminal ends of the parental peptide PiP01. P156 was highly potent and eradicated all tested strains of C. acnes and S. aureus. P156 acted rapidly (>5-log kill in 10 min), further reducing the potential of resistance development. Additionally, P156 maintained its potency under conditions (e.g., temperature, pH, and salt concentration) observed on the skin surface and in hair follicles, as well as in combination with retinoid—all without being toxic to human cells. Conclusions: These collective findings position P156 as a promising topical drug for clinical applications to control acne vulgaris.